AN OPEN-SOURCE MANUFACTURING EXECUTION SYSTEM - Folorunso, Oluwaseun (My University, 2024)
Industry 4.0, also known as the 4th industrial revolution, represents the integration of the entire product lifecycle in manufacturing, involving both vertical and horizontal connectivity. A key aspect of Industry 4.0 is the interconnection of all devices within a manufacturing process, enabling data exchange both horizontally between devices and vertically across different departments in a company. This necessitates the development of automation models that govern data collection, sharing, and utilization throughout the product lifecycle. The Automation Pyramid, comprising 4 to 6 layers, plays a crucial role in achieving this integration. The ANSI/ISA-95 international standard, established by the International Society of America (ISA), guides the integration of business enterprise systems (ERP) with shop floor operations. Manufacturing Execution Systems (MES) emerged in the 1990s as a solution to the limitations of ERP systems, aiming to bridge the gap between ERP and shop floor operations. While MES systems are vital for achieving Industry 4.0 goals, many companies hesitate to integrate them due to cost and integration complexity making them prohibitive for small to medium-sized enterprises (SMEs). This study seeks to address this challenge by developing an affordable MES solution tailored for SMEs, providing a cost-effective means to transition to Industry 4.0. The solution aims to act as a stepping stone into the realm of Smart Manufacturing with Industry 4.0 without necessitating a complete replacement of existing MES systems